PP2A-B55SUR-6 promotes nuclear envelope breakdown in C. elegans embryos - Sukriti Kapoor; Kuheli Adhikary; Sachin Kotak (Cell Reports, 2023)
Summary: Nuclear envelope (NE) disassembly during mitosis is critical to ensure faithful segregation of the genetic material. NE disassembly is a phosphorylation-dependent process wherein mitotic kinases hyper-phosphorylate lamina and nucleoporins to initiate nuclear envelope breakdown (NEBD). In this study, we uncover an unexpected role of the PP2A phosphatase B55SUR-6 in NEBD during the first embryonic division of Caenorhabditis elegans embryo. B55SUR-6 depletion delays NE permeabilization and stabilizes lamina and nucleoporins. As a result, the merging of parental genomes and chromosome segregation is impaired. NEBD defect upon B55SUR-6 depletion is not due to delayed mitotic onset or mislocalization of mitotic kinases. Importantly, we demonstrate that microtubule-dependent mechanical forces synergize with B55SUR-6 for efficient NEBD. Finally, our data suggest that the lamin LMN-1 is likely a bona fide target of PP2A-B55SUR-6. These findings establish a model highlighting biochemical crosstalk between kinases, PP2A-B55SUR-6 phosphatase, and microtubule-generated mechanical forces in timely NE dissolution.